LEMBAGA PENDIDIKAN KAUM SUFI ZAWIYAH, RIBATH DAN KHANQAH - Muhammad Faizul Amirudin (El-Ghiroh : Jurnal Studi Keislaman, 2017)
The institutions for non-formal education before the period madrassa showed concern for the importance of education for citizens who showed the dynamics of Islamic education is very dynamic, and it showed a model of democratic education, freely controlled even tolerance. Educational institutions that include mosques, al-Kutab, Zawiyah, Ribath, Khanaqah and